The Heuristic Algorithm Optimization of Home Care Path Based on the Internet of Things Realizes Connected Medical Care - Zhang, Jinfeng; Li, Xin; Zhao, Yu (Computational and mathematical methods in medicine, 2022)
Optimize the scheduling problem of family nursing staff according to the actual needs of the customers, combined with the psychological behavior characteristics of the participants, and use the path heuristic algorithm on home nursing service institutions, full-time nursing staff, and nursing customers. Taking this as the maximization of the three subjects as the ultimate goal of home caregiver optimization and scheduling, a path heuristic-based heuristic optimization and scheduling method (path heuristic algorithm, PHA). The effectiveness of this method is analyzed through examples, and finally, according to the experimental analysis results of the distribution, dominance, and convergence of the proposed PHA algorithm, the home caregiver optimization and scheduling method proposed in this paper can provide a more long-term scheduling method for enterprise companies.